2015
DOI: 10.4103/0255-0857.148373
|View full text |Cite
|
Sign up to set email alerts
|

Complete sequencing of an IncX3 plasmid carrying blaNDM-5 allele reveals an early stage in the dissemination of the blaNDM gene

Abstract: This is the first report where the blaNDM gene insertion in a plasmid is not accompanied by other resistance gene determinants. These observations suggest that the IncX3 plasmid pNDM-MGR194 is an early stage in the dissemination of the blaNDM .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 29 publications
(37 reference statements)
5
56
0
Order By: Relevance
“…bla was carried by an IS26-dsbC-trpF-ble MBL -bla NDM-7 -⌬ISAba125-IS5-⌬ISAba125 genetic element; this is the same structure as that of the bla NDM-4 -and bla NDM-5 -containing elements reported previously (34,35) and is similar to the bla NDM-7 plasmid described from Germany (27). The overall plasmid genome synteny in pKpN01-NDM7 is also identical to that of bla NDM-5 -harboring pNDM_MGR194 (from a ST11 K. pneumoniae isolate in India) (34) and bla NDM-4 -harboring pJEG027 (from a K. pneumoniae isolate in Australia) (35). Importantly, IS5 was inserted into ISAba125 located upstream of bla NDM , leading to the interruption of ISAba125 into two segments (1,018 bp and 73 bp) (Fig.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…bla was carried by an IS26-dsbC-trpF-ble MBL -bla NDM-7 -⌬ISAba125-IS5-⌬ISAba125 genetic element; this is the same structure as that of the bla NDM-4 -and bla NDM-5 -containing elements reported previously (34,35) and is similar to the bla NDM-7 plasmid described from Germany (27). The overall plasmid genome synteny in pKpN01-NDM7 is also identical to that of bla NDM-5 -harboring pNDM_MGR194 (from a ST11 K. pneumoniae isolate in India) (34) and bla NDM-4 -harboring pJEG027 (from a K. pneumoniae isolate in Australia) (35). Importantly, IS5 was inserted into ISAba125 located upstream of bla NDM , leading to the interruption of ISAba125 into two segments (1,018 bp and 73 bp) (Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Since then, IncX3 plasmids containing different bla NDM alleles, including bla NDM-1 , bla NDM-4 (e.g., pJEG027), bla NDM-5 (e.g., pNDM_MGR194), and bla NDM-7 (e.g., pKpN01-NDM7 [current study] and pOM26-1) have been reported from different geographical regions (e.g., China, India, Australia, Germany, Canada, and Oman) and in different species (34)(35)(36)44), dramatizing the significant role played by plasmids in the rapid worldwide dissemination of NDM-type carbapenemases. Our study showed that NDM-7 is present in several Enterobacteriaceae genera isolated in the Calgary region due to a single identical bla NDM-7 -harboring IncX3 plasmid, pKpN01-NDM7.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The NDM-5-encoding gene bla was first identified in an Escherichia coli strain recovered from a patient in the United Kingdom in 2011 (3). Since then, bla was identified in many countries, such as Algeria (4)(5)(6), the United States (7), Australia (8), China (9)(10)(11)(12), Denmark (13), Japan (14), India (15), and the United Kingdom (3). The widespread occurrence of NDM-5 in recent years should arouse our attention.…”
mentioning
confidence: 99%
“…Moreover, the genetic environment (IS5-ΔISAba125-bla NDM-1 -ble MBL -trpF-cutA-groES-groEL) of the bla NDM-1 gene was identical to that found in various bla NDM-1 -carrying plasmids in Enterobacteriaceae in China. As one major type of IncX plasmids, IncX3, containing different bla NDM alleles, including bla NDM-1 , bla NDM-4 , bla , and bla NDM-7 , has been reported in different geographic regions and in different species, highlighting the role played by plasmids of this replicon type in the global dissemination of NDM-type carbapenemases (17)(18)(19).…”
mentioning
confidence: 99%